2013
DOI: 10.1371/journal.pmed.1001566
|View full text |Cite
|
Sign up to set email alerts
|

Timing and Completeness of Trial Results Posted at ClinicalTrials.gov and Published in Journals

Abstract: Agnes Dechartres and colleagues searched ClinicalTrials.gov for completed drug RCTs with results reported and then searched for corresponding studies in PubMed to evaluate timeliness and completeness of reporting. Please see later in the article for the Editors' Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
179
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(203 citation statements)
references
References 33 publications
11
179
0
2
Order By: Relevance
“…However, we are aware of the fact that this may be biased by the respective authors that tend to underestimate or undervalue negative results, for instance in comparison to registered trial reports. 81,82 We found that 14 of the 27 studies reported negative outcome on global symptoms, however individual symptoms (bloating 67,77 and satiety 69 ) were occasionally reported as being responsive to treatment. Quality of life (QoL) improved in one study but symptomatic improvement was not different from placebo.…”
Section: Global Outcomementioning
confidence: 87%
“…However, we are aware of the fact that this may be biased by the respective authors that tend to underestimate or undervalue negative results, for instance in comparison to registered trial reports. 81,82 We found that 14 of the 27 studies reported negative outcome on global symptoms, however individual symptoms (bloating 67,77 and satiety 69 ) were occasionally reported as being responsive to treatment. Quality of life (QoL) improved in one study but symptomatic improvement was not different from placebo.…”
Section: Global Outcomementioning
confidence: 87%
“…12 For such analyses, the publication date was the date reported after the wording "results first received" for the unpublished trials; the earlier of either the publication date or the date that the results were made available on ClinicalTrials.gov for published trials.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Posting results on registry websites does not negate the importance of peer reviewed publication, 43 44 but our data show that ClinicalTrials.gov can serve a useful role in enhancing the completeness of available information. 12 Some considerations on the search for published reports are needed. A previous survey 20 found that a substantial proportion of randomized controlled trials (40-45%) is still being published without the reporting of a trial registration code, thereby weakening the ability of the researchers to identify multiple publications of the same trial, cross check the published report with the original design, and investigate selective reporting.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…Alarge percentage ofclinical trial resultsremainunpublishedinthe biomedical literature long after their data reach maturity [1][2][3][4][5][6]. In few areas of medicine is the timely dissemination of clinical trial results more crucial than in oncology, because this knowledge is used to optimize dynamic treatment decisions, often involving the ongoing, off-label use of drugs already approved [7].…”
Section: Introductionmentioning
confidence: 99%